Ambulatory surgery centers: possible solution to improve cataract healthcare in medical deserts. Issue 3 (March 2021) - Bigoteau, Maxime; Grammatico-Guillon, Leslie; Massot, Michel; Baudet, Jean-Marie; Cook, Ann-Rose; Duroi, Quentin; Pichard, Tiphanie; Slim, Malek; Pisella, Pierre-Jean; Khanna, Raoul Kanav
Abstract : Ambulatory cataract surgery centers, providing a fast-track procedure that does not require anesthetic monitoring, could represent a solution for the improvement of cataract healthcare in medical deserts, without supplementary funding. Abstract : Purpose: To investigate the epidemiological impact of an ambulatory cataract surgery center providing a fast-track procedure without anesthetic evaluation on the access to cataract healthcare. Setting: French nationwide study. Design: Retrospective cross-sectional study. Methods: The study included individuals undergoing cataract surgery from the French national administrative database of medical information. Data analyses focused on patients living in the Cher and neighboring areas. Epidemiological indicators of patient flow and healthcare efficiency were calculated. A medicoeconomic analysis was performed. Results: Between 2012 and 2018, activity increased by +50.2% (3665 to 5506) interventions in the Cher area compared with a national increase of +22.7% (720 351/884 254), while maintaining a constant ophthalmologist workforce. The leakage ratio decreased by 5.9 points (26.3% to 20.4%), whereas the attractiveness and self-sufficiency ratios increased by 2.3 (8.6% to 10.9%) and 8.6 (80.6% to 89.2%) points, respectively. The age- and sex-standardized rate of healthcare utilization for cataract surgery increased by 4.3 points (11.6 to 15.9 cataract surgeries per 1000 inhabitants), making the Cher the second best French area in 2018 for the rate of cataract surgery despite ranking 96th of 109 French areas for ophthalmologist density. The cost of the cataract removal procedure was 523.99€ (666.22€ in the conventional operating room). Conclusions: An ambulatory cataract surgery center with a fast-track procedure could represent a solution in medical deserts to improve cataract healthcare without supplementary funding. Nonetheless, consulting activity should be optimized to detect eye disorders and schedule interventions.